Sodium chlorate as a viable substoichiometric oxidant for cobalt-catalyzed oxidative annulation of aryl sulfonamides with alkynes. Issue 30 (27th July 2016) - Ran, You; Yang, Yudong; Zhang, Luoqiang
Graphical abstract: Highlights: Synthesis of sultams through cobalt-catalyzed oxidative annulation. NaClO3 proved to be a versatile oxidant in C–H activation reaction. Moderate to excellent yields with excellent regioselectivity could be obtained. A broad scope of functional groups could be tolerant. Abstract: In this work, NaClO3 is demonstrated for the first time as an efficient and versatile oxidant in the catalytic C–H activation reaction. By using sodium chlorate as the oxidant, a highly regioselective cobalt-catalyzed oxidative annulation of aryl sulfonamides with alkynes has been developed and can be extended to the annulation of benzamide.